Paradigma Baru Pembentukan dan Analisis Peraturan Daerah (Studi Atas Perda Pelayanan Publik dan Perda Keterbukaan Informasi Publik) - Jazim Hamidi (Jurnal Hukum IUS QUIA IUSTUM, 2011)
Reformation in 2008 has changed the state paradigm of Indonesia from centralistic into decentralized government by widely implementing the autonomy concept. This change has also brought the influence in establishment and analysis of Local Regulation based on the concepts of Rocippi, Fish Bone, or RIA that are representative of the old paradigm to the new one that is the concept of SDER (Sustainable, Development, and Engineering Regulation). This research applies the judicial-normative method through a regulation approach. Meanwhile, the analysis method used to solve the existing legal issues is the qualitative-judicial method. The result of the research on two PERDA (the Local Regulations) - which is about Public Service and Openness of Public Information – concludes that by implementing the concept of SDER, the paradigm in establishment of both the State Oriented Local Regulation and civilized oriented Local Regulation could be turned into the Integrated Local Regulation; namely State and Civilized Integrated Oriented Local Regulation. The legal implication of this concept is that the Program of Local Legislation must be oriented to the struggle of the local regulation reform that can prosper the people.